SMART POLYMER NANOCOMPOSITES: RECENT ADVANCES AND PERSPECTIVES - Bruno F. Urbano; Claudio Mella; Myleidi Vera (Journal of the Chilean Chemical Society, 2020)
Nanocomposite polymers have received considerable interest in research for the last three decades. Those nanocomposite polymers that are sensitive to a stimulus such as pH, temperature, magnetism, and electricity, among others, called smart or intelligent nanocomposite polymers had received even greater attention due to their potential technological applications. Applications of these polymers include flexible electronic devices, sensors, self-healing polymers, shape-memory materials, etc. The material's sensitivity can come from both the polymer that acts as a matrix and the nanofiller, resulting in a material that combines properties of each of its components and that each one will not have separately. This mini-review aims to provide an update on the most recent and significant applications in the area of stimuli-responsive polymer nanocomposites, emphasizing the most innovative applications developed in the last three years.